Perancangan Sistem Keamanan Jaringan TCP/IP Berbasis Virtual LAN Dan Access Control List - Istiqlal, Muhammad Ariq; Sari, Linna Oktaviana; Ali, Irsan Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Internet network that has been developed at this time is a network architecture based on TCP / IP.Each layer of the TCP / IP on the Internet provides an opportunity for a security hole. One of manyways of closing the security hole is to set the Access Control List (ACL) on the Internetwork layer.ACL is used to permit or deny the package from the host towards a specific purpose. ACL consistsof rules and conditions that determine and define the process network traffic at the router whetherthe package will be passed or not. Methods ACL is created on an existing VLAN network, thusincreasing the security of the network. Results of this research is with implement an ACL can blockinternet sites that can not be accessed by the user in a network. Then by applying ACL on VLAN,the access rights of a user on the network can be segmented, thus reducing the chance of spreading